The Influence of the Board of Independent Commissioners, Audit Committee, and Managerial Ownership on Financial Performance in Manufacturing Companies Listed on the Indonesia Stock Exchange. - Muhammad Teguh; Mareta Suwartini; Indina Azzahra; Marlena Susanti (Systematic Literature Review Journal, 2025)
Good Corporate Governance (GCG) refers to the practices and processes that guide a company's operations and decision-making, significantly influencing its financial performance. This study employs secondary and quantitative data, utilizing the Systematic Literature Review (SLR) method, with sources obtained from the Google Scholar website. The research focuses on the impact of the Independent Board of Commissioners, the Audit Committee, and Managerial Ownership on financial performance. The findings indicate that effective corporate governance, particularly the presence of an independent Board of Commissioners, positively influences financial performance as assessed by Return on Assets (ROA). Additionally, the Audit Committee is shown to have a significant and positive effect on financial performance. In contrast, while Managerial Ownership does not appear to impact financial performance when evaluated through ROA, it does exhibit a positive correlation when assessed using Tobin's Q. This suggests that higher managerial ownership can enhance market perceptions of the company's long-term value and stability. The study concludes that the successful implementation of Good Corporate Governance practices can lead to improved financial performance for companies. Conversely, inadequate execution of these governance principles may result in diminished financial performance and overall company value. Therefore, it is crucial for organizations to prioritize and effectively implement GCG to foster better financial outcomes and enhance their market standing. This research underscores the importance of governance structures in shaping financial results and highlights the need for companies to focus on governance practices to achieve sustainable growth and value creation. Ultimately, the study emphasizes that a strong commitment to GCG can lead to increased investor confidence and long-term success in the competitive business landscape.